Preconception micronutrient supplementation positively affects child intellectual functioning at 6 y of age: A randomized controlled trial in Vietnam - Nguyen, Phuong Hong; Young, Melissa F.; Tran, Lan Mai; Khương, Long Quỳnh; Duong, Thai Hong (American Society for Nutrition, 2021)
Although there is growing evidence on the role of preconception nutrition for birth outcomes, very few studies have evaluated the long-term effects of nutrition interventions during the preconception period on offspring cognitive outcomes.